In Situ Grown Tungsten Trioxide Nanoparticles on Graphene Oxide Nanosheet to Regulate Ion Selectivity of Membrane for High Performance Vanadium Redox Flow Battery. (9th November 2021) - Ye, Jiaye; Zheng, Chunhua; Liu, Jie; Sun, Tianfu; Yu, Shuhui; Li, Huiyun
Abstract: The application of vanadium redox flow batteries (VRFBs) has encountered challenges because the most commonly used commercial membrane (perfluorinated sulfonic acid, PFSA) has severe vanadium ion permeation, which yields poor stability of the battery. Herein, a PFSA‐based hybrid membrane with a sandwich structure created using a reinforced polytetrafluoroethylene thin layer with hydrophilic nanohybrid fillers is developed. The tungsten trioxide (WO3 ) nanoparticles are in situ grown on the surface of graphene oxide (GO) nanosheets to overcome the electrostatic effect, and to enhance the hydrophilicity and dispersibility of GO nanosheets, which is embedded in the PFSA matrix to act as a "barrier" to reduce vanadium ions permeation. In addition, these hydrophilic WO3 nanoparticles on GO nanosheets surface serve as proton active sites to facilitate proton transportation. As a result, at 120 cm −2, the cell of the hybrid membrane displays high Coulombic efficiency (over 98.1%) and high energy efficiency (up to 88.9%), better than the commercial Nafion 212 membrane at the same condition. These performances indicate the proposed hybrid membrane is applicable for VRFB application. Also, this design method of the membrane can be extended to other fields including water treatments and fuel cells. Abstract : A perfluorinated sulfonic acid‐based hybrid membrane is prepared with tungsten trioxide@graphene oxide (GO) nanohybrids and a polytetrafluoroethylene reinforced‐layer. The nanohybrids block vanadium ions permeation effectively. The nanoparticles on the surface of GO nanosheets provide more paths for protons transportation. The vanadium redox flow battery of the hybrid membrane displays excellent energy efficiency and good cyclicity.